2015
DOI: 10.1155/2015/129034
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines as Mediators of Pain‐Related Process in Breast Cancer

Abstract: Pain is a clinical sign of inflammation found in a wide variety of chronic pathologies, including cancer. The occurrence of pain in patients carrying breast tumors is reported and is associated with aspects concerning disease spreading, treatment, and surgical intervention. The persistence of pain in patients submitted to breast surgery is estimated in a range from 21% to 55% and may affect patients before and after surgery. Beyond the physical compression exerted by the metastatic mass expansion and tissue in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 49 publications
0
26
0
2
Order By: Relevance
“…Recently we have demonstrated that the positive and negative estrogen tumors show different metabolic patterns ( manuscript in press ). Finally, tumors that do not exhibit any of these receptors are classified as triple negative [21]. Breast cancer develops within a specialized tumor microenvironment that consists of numerous cell types including cancer cells, stromal cells, adipose, and infiltrating immune cells.…”
Section: “Cytokinome” and Breast Cancermentioning
confidence: 99%
“…Recently we have demonstrated that the positive and negative estrogen tumors show different metabolic patterns ( manuscript in press ). Finally, tumors that do not exhibit any of these receptors are classified as triple negative [21]. Breast cancer develops within a specialized tumor microenvironment that consists of numerous cell types including cancer cells, stromal cells, adipose, and infiltrating immune cells.…”
Section: “Cytokinome” and Breast Cancermentioning
confidence: 99%
“…Modulation of epigenetic markers represents the novelty of cancer-related research, and PTX may also regulate the expression of certain microRNAs (miRNAs) associated with cancer progression. Furthermore, PTX can exert a variety of positive influences on the modulation of immune response via regulation of chemokines, cytokines, or immune cells [11,12]. The resistance of BC to PTX and other chemotherapeutics as a consequence of disequilibrium in various signaling pathways, mutations in certain genes, and epigenetic deregulations is responsible for the worse clinical outcome for patients with BC [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, significant increases in the plasma levels of proinflammatory cytokines (TNF-α, IL-1b, IL-6 and IL-8) are found in patients with intestinal disorders favoring mucosal inflammation, including constipation-predominant IBS [51,52]. This correlation can be explained by the sustained stimulation of nociceptors in chronic pain by proinflammatory cytokines pathway, resulting in local hypersensitivity, hypersensitivity in the adjacent regions and increased Central Nervous System responsiveness through chemical, physical or mechanical stimuli [53,54].…”
Section: Discussionmentioning
confidence: 99%